Pengaruh Pengembangan Organisasi dan Perilaku Kerja terhadap Peran Bidan dalam Pencegahan Tindakan Ibu terhadap Penularan Anak (PMTCT) dan Kemandirian Asuhan Ibu Hamil di Masa Pandemi Covid-19 - Iin Octaviana Hutagaol (Maternal & Neonatal Health Journal, 2022)
This research was motivated by pregnant women who endured HIV/AIDS during the Covid-19 pandemic. Their self-sufficiency was low or very low because they were incapable generate a readiness to prevent and overcome the disease problems they suffered. The theory of reasoned action (TRA) developed into the theory of planned behavior (TPB). This conceptual framework refers to combining the Kopelmen's with the theory of planned behavior (TPB) in influencing midwives in PMTCT actions on HIV AND AIDS care independence. Data analysis uses Structural Equation Model analysis - SEM. It combines several aspects contained in path analysis and confirmatory factor analysis to estimate several equations simultaneously. The study found that organizational characteristics (X1) effect on the midwives' role (Y) had a positive and significant effect. The work characteristics (X2) effect on midwives' role (Y) is positive and significant. The organizational characteristics (X1) effect on the pregnant women's independence (Z) is positive and not significant. The work characteristics (X2) on the independence of pregnant women (Z) have a positive and significant effect, and the role of midwives (Y) on the independence of pregnant women (Z) has a positive and significant effect. The result of the indirect effect shows that organizational characteristics (X1) through the role of the midwife (Y) have a positive and insignificant effect on the independence of pregnant women (Z), and work behavior (X2) through the role of the midwife (Y) has a positive and significant effect on the independence of pregnant women ( Z). Research recommends improving the reward system, training, and development as well as the leadership of each midwife. To carry out their duties and functions of providing health services to HIV and AIDS care in each Puskesmas as a form of organizational characteristics that affect the role of midwives in PMTCT actions in Makassar City. Maintaining the achievement of performance goals and the resulting feedback as work characteristics of midwives that will affect the role of midwives in PMTCT actions in Makassar City.